Access to anticancer medicines in public hospitals of Northwestern China - Yue Ma; Yue Ma; Yue Ma; Yue Ma; Jin Peng; Jin Peng; Jin Peng; Jin Peng; Xuelin Yao; Xuelin Yao; Xuelin Yao; Xuelin Yao; et al. (Frontiers Media S.A., 2023)
ObjectiveWe aimed to evaluate the accessibility of anticancer medicines in public hospitals of Shaanxi, a representative province of Northwestern China.MethodsThirty-one anticancer medicines were investigated in 146 designated public hospitals in 10 cities of Shaanxi Province. We used medicine procurement data from the Shaanxi Drug Centralized Purchasing Platform during 2019-2021. Primary outcomes included the availability, drug utilization, and affordability of anticancer medicines.ResultsThe mean availability of 31 anticancer medicines increased significantly from 5.45% in 2019 to 14.72% in 2021. The mean availability of nationally negotiated medicines was significantly lower than that of Class B medicines (8.72% vs. 12.85%, p = 0.048), whilst the availability of injectable medicines was significantly greater than that of oral medicines (13.66% vs. 8.77%, p = 0.007). In 2019-2021, the annual mean amount purchased increased significantly from CNY 6.51 million to CNY 18.56 million (p = 0.007). The mean defined daily doses of 31 medicines significantly rose from 225.50 to 1019.50 (p = 0.008) whereas their defined daily drug cost significantly decreased from CNY 551.15 to CNY 404.50 (p < 0.001). The percentage of catastrophic health expenditure decreased from 71.0 to 51.65% and from 90.30 to 80.60% for urban and rural residents, respectively. The affordability of nationally negotiated medicines was significantly lower than that of Class B medicines (p = 0.032), and the affordability of injectable medicines had no significant difference compared to that of oral medicines (p = 0.124) for both urban and rural residents.ConclusionThe accessibility of anticancer medicines improved dramatically in public hospitals of Northwestern China during the period 2019-2021.